2017
DOI: 10.1007/s10339-017-0839-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three different regimens of repeated methamphetamine on rats’ cognitive performance

Abstract: Neurocognitive impairment in response to methamphetamine (MA) has been proven in a variety of experimental and clinical studies. Elucidation of the underlying mechanisms of MA-induced cognitive deficits and finding preventive/therapeutic approaches need best-suited animal models. In modeling repeated MA exposure, while some believes that escalating doses simulate drug abuse conditions, others believe this regimen confers a preconditioning protection. The present study aimed to compare the effects of three diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Since METH exposure can also lead to poor performances in other cognitive phenotypes, 35,37–39 we also conducted a Y‐maze test to further confirm the neuroprotective effects of KOR antagonist (Figure 7A,B). We found that METH decreased number (Figure 7E, F (2, 33) = 6.921, p = 0.0031) and rate of spontaneous alteration (SAP) (Figure 7F, F (2, 33) = 13.33, p < 0.0001) and increased incorrect same arms returns (SAR) (Figure 7D, F ((2, 33) = 4.995, p = 0.0127), which was reserved by norBNI microinjections into PL before METH treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since METH exposure can also lead to poor performances in other cognitive phenotypes, 35,37–39 we also conducted a Y‐maze test to further confirm the neuroprotective effects of KOR antagonist (Figure 7A,B). We found that METH decreased number (Figure 7E, F (2, 33) = 6.921, p = 0.0031) and rate of spontaneous alteration (SAP) (Figure 7F, F (2, 33) = 13.33, p < 0.0001) and increased incorrect same arms returns (SAR) (Figure 7D, F ((2, 33) = 4.995, p = 0.0127), which was reserved by norBNI microinjections into PL before METH treatment.…”
Section: Resultsmentioning
confidence: 99%
“…After 24 h of last METH injections, a Y‐maze spontaneous alternation behaviour test (SAB) was conducted to assess the spatial memory of mice 35 . The Y‐maze consisted of three identical Plexiglas arms (30 cm length × 6 cm width × 15 cm height), labelled A, B, C and orientated at 120° angles from each other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the current illicit drugs, METH is the most prevalent illicit drug in numerous countries, including China (Bramness et al, 2015; Kwon and Han, 2018; Bannwarth et al, 2019). METH abuse has been shown to result in cognitive deficits in attention, learning, and memory in a variety of experimental and clinical studies (Potvin et al, 2018; Seyedhosseini Tamijani et al, 2018). Several dose regimens of METH administration have been evaluated in different studies, such as a single high dose (40 mg/kg) or repeated (4 × 10 mg/kg, 2–3-h intervals) or escalating (1–10 mg/kg, twice a day, at 5-h intervals, for 10 days) doses of METH and chronic voluntary oral METH intake (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a 12-week aerobic exercise may have beneficial effects on METH dependent patients with verbal learning and memory deficits [78]. In animal studies, chronic METH treatment could also impair cognitive functions [79][80][81][82][83], including deficits in reversal learning [79], disorders in alert exploratory behavior [80], impairments in recognition memory [81] and so on. In addition, Seyedhosseini et al [82] pointed out that repeated METH administration impaired only long-term recognition memory in somehow dose dependent manner while short-term remained unchanged.…”
Section: Methamphetamine (Meth)mentioning
confidence: 99%